The validity and reliability of Indonesian version of atrial fibrillation effect on quality of life (AFEQT) questionnaire for atrial fibrillation patients - Putri Zulmiyusrini; Muhammad Yamin; Muhadi Muhadi; Juferdy Kurniawan; Simon Salim (SpringerOpen, 2023)
Abstract Background More than 60% of patients with atrial fibrillation (AF) have a significant health-related quality of life (HRQoL) impairment. HRQoL, a patient-reported outcome (PRO), has become an important endpoint to assess treatment success in AF patients. The Atrial Fibrillation Effect on Quality of Life (AFEQT) questionnaire is an AF-specific HRQoL tool shown to be feasible, reliable, and valid, with translations in various languages. Since this questionnaire has never been translated or validated in Indonesian, we aimed to determine the validity and reliability of the Indonesian version of the AFEQT questionnaire for AF patients. Results This cross-sectional, observational study was conducted in the Integrated Cardiovascular Service Polyclinic, Cipto Mangunkusumo Hospital, Indonesia, from December 2021 to March 2022. A total of 30 participants were recruited for cross-cultural adaptation process, which consisted of translation and adaptation process, and a total of 102 participants were consecutively recruited to participate in the validation process, which consisted of validity test (construct validity) and reliability tests (internal consistency and test-retest). The retest was conducted within a 1-2-week interval after the baseline assessment, by analyzing the intraclass correlation coefficient (ICC). The construct validity was determined by multitrait scaling analysis, and the convergent and divergent validity was compared to SF-36 domains. Multitrait scaling analysis revealed that all items in the Indonesian version of the AFEQT questionnaire had a strong negative correlation towards their respective domains (r -0.639--0.960). For convergent and divergent validity, AFEQT domains had weak to strong positive correlations to all SF-36 domains (r 0.338-0.693). This questionnaire also had acceptable internal consistency (Cronbach's α for overall score: 0.947; Domains: Symptoms: 0.818, Daily Activities: 0.943, Treatment Concern: 0.894, and Treatment Satisfaction: 0.865), as well as moderate-to-good test-retest reliability (0.521-0.828). Conclusions The Indonesian version of the AFEQT questionnaire has good validity and reliability for assessing quality of life of atrial fibrillation patients in Indonesia.